Expansion in eigenfunctions of relations generated by pair of operator differential expressions - Khrabustovskyi, V. (Methods of Functional Analysis and Topology, 2009)
For relations generated by a pair of operator symmetric differential expressions, a class of generalized resolvents is found. These resolvents are integro-differential operators. The expansion in eigenfunctions of these relations is obtained.